Exchange Rate Choices with Inflexible Markets and Costly Price Adjustments - Iyer, Tara (IMF Working Papers; Working Paper ;, 2017)
This paper analyzes the appropriate choice of an exchange rate regime in agricultural commodity-exporting economies. In an open economy model that incorporates key structural characteristics of agricultural commodity exporters including dual labor markets, the benefits of exchange rate flexibility are shown to depend on the extent of labor and product market development. With developed markets, flexible exchange rates are preferred as they allow for greater relative price fluctuations, which amplify the transmission mechanism of labor reallocation upon commodity price volatility. When labor and product markets are not welldeveloped, however, international relative price adjustments exacerbate currency and factor misalignments. A nominal exchange rate peg, by mitigating relative wage and price fluctuations, increases welfare relative to a float. Given the current low level of labor and product market development across most agricultural commodity exporters, the study provides a counterpoint to conventional arguments in favor of flexible exchange rates and a rationale as to why exchange rate targeting is appropriate in agricultural economies.